STUDENTS’ PERCEPTION ON READING INTEREST BY USING ENGLISH INFOGRAPHIC IN ONLINE CLASS - Muhammad Galuh Elga Romadhon (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Reading is one of the skills in English that can help the readers find the information and increase their skills. The formulated research problems were: 1) what is the students’ perception of using English infographics in reading online classes? 2) How can the English infographic assist the students to be interested in reading English text? Based on this research problems above, the objective of research was 1) to describe the students’ perception about using English infographic during reading online class, 2) to investigate whether the use of English infographics can assist the students’ reading interest in English text. The research design in this research was a descriptive qualitative design with a qualitative approach. The subject of this research was students of the first semester at Reading 1 class in the English education department of University of Islam Malang. The data analysis used two ways: inscribe the data, analyze the data, and interpret the data. The finding of this research is the students have positive perception about using infographic as a reading media in the online class. Then, the infographic also can increase the students’ reading interest.